PENGARUH FAKTOR FUNDAMENTAL DAN RISIKO (BETA) TERHADAP RETURN SAHAM PADA PERUSAHAAN YANG TERMASUK DALAM INDEKS LQ 45 - Diah Ismayanti; Meina Wulansari Yusniar (Universitas Lambung Mangkurat, 2014)
This study aims to investigate the influence of fundamental factors (DER, ROE, PER, EPS and NPM) and risk (Beta) on stock returns of companies included in the index LQ 45. The study sample consisted of 17 companies which for 4 years in a row including the LQ 45. The statiscaly methods used to test the hypothesis in this study, is multiple linear regression technique and obtained the following results: Simultaneous way, all independent variables used in this study affect the stock returns of companies included in the index LQ 45. 2. Partially independent variables which affect the stock returns of companies included in the index is variable LQ 45 Debt Equity Ratio (X1), Earning Per Share (X4), Net Profit Margin (X5) and Beta (X6). Return on Equity (X2) and Price Earning Ratio (X3) variable had no effect on stock returns of companies included in the index LQ 45